2019
DOI: 10.1016/j.jcbs.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of relational responding and a healthy self in older adolescents

Abstract: Evidence from Contextual Behavioral Science indicates that two patterns of relating facilitate a sense of self, namely, self-as-distinction and self-as-hierarchy. Although the latter has been associated with better mental health outcomes relative to self-as-distinction, to date these types of relating have not been examined directly at a baseline level, wherein manipulation has not occurred. The present study examined the relative contribution of self-as-distinction and self-as-hierarchy on depression, stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
2
7
2
Order By: Relevance
“…Subsequent research has shown that improvement due to training on the ability to reverse deictic relations does not necessarily change Theory of Mind performance (Montoya-Rodríguez & Molina-Cobos, 2016) and that the details of training matter. From an operant perspective, these findings give broad support to the idea that we can treat ToM as a series of relational (deictically-involved) operant classes but they also emphasize that the details of the specific relations appear to matter, not just as a means of shaping ToM skills, but in the management of other areas of human complexity such as how emotions are described or addressed by behavior (Moran & McHugh, 2019).…”
Section: Development and Shapingsupporting
confidence: 55%
See 1 more Smart Citation
“…Subsequent research has shown that improvement due to training on the ability to reverse deictic relations does not necessarily change Theory of Mind performance (Montoya-Rodríguez & Molina-Cobos, 2016) and that the details of training matter. From an operant perspective, these findings give broad support to the idea that we can treat ToM as a series of relational (deictically-involved) operant classes but they also emphasize that the details of the specific relations appear to matter, not just as a means of shaping ToM skills, but in the management of other areas of human complexity such as how emotions are described or addressed by behavior (Moran & McHugh, 2019).…”
Section: Development and Shapingsupporting
confidence: 55%
“…Historically, research on perspective-taking has been densely limited to fields such as cognitive and developmental psychology, especially when cross-sectional developmental profiles have been employed. Behavior analytic studies using perspective-taking training have been growing, however (McHugh et al, 2009;Moran & McHugh, 2019).…”
Section: Development and Shapingmentioning
confidence: 99%
“…If self as content is a solid domination of appointed content, “self as process” can be considered a more flexible flow of such content and of the human experience more generally. Self as process comes into being as an integral part of living a vital life ( Moran & McHugh, 2019 ). As time flies by, individuals pass from instant to instant throughout their life.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of this study is that the direction of causality could also be reversed, in that reductions in outcomes such as depression could also have led to the improvements in self as context / perspective-taking. Moran and McHugh (2019) showed that for non-clinical adolescents, framing the self hierarchically with psychological experience was associated with reduced stress, depressed mood and avoidance behaviour, whilst framing the self with only distinction relations was not. Finally, Moran, Almeida and McHugh (2018) found in a cross-sectional analysis of nonclinical participants, that measures of self as content, self as process and self as context all independently predicted poorer mental health in theoretically hypothesised directions.…”
Section: Relational Frame Theory and Perspective-takingmentioning
confidence: 98%
“…This kind of framing leads to the experience of 'self as story' or 'conceptualised self' (also called 'self as content') in ACT. RFT postulates that in self as story, psychological content and 'I' are framed in coordination and both in the here and now (Moran & McHugh, 2019).…”
Section: Relational Frame Theory and Perspective-takingmentioning
confidence: 99%